2016
DOI: 10.1016/j.ajpath.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-11 Receptor Is a Candidate Target for Ligand-Directed Therapy in Lung Cancer

Abstract: We previously isolated an IL-11emimic motif (CGRRAGGSC) that binds to IL-11 receptor (IL-11R) in vitro and accumulates in IL-11Reexpressing tumors in vivo. This synthetic peptide ligand was used as a tumortargeting moiety in the rational design of BMTP-11, which is a drug candidate in clinical trials. Here, we investigated the specificity and accessibility of IL-11R as a target and the efficacy of BMTP-11 as a ligandtargeted drug in lung cancer. We observed high IL-11R expression levels in a large cohort of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Our group demonstrated that it is possible to proceed rapidly from discovery in humans (3) to preclinical validation (16,17) to a first-in-human clinical trial (18). From four ligand-receptors identified in terminal patient, two are ubiquitous and previously reported (integrin α4/annexinA4 and cathepsin B/apolipoprotein E3) and the other two are specific to white adipose tissue (WAT) (prohibitin/annexin A2) (19) and tumor tissues (RAGE/PR3) (4), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Our group demonstrated that it is possible to proceed rapidly from discovery in humans (3) to preclinical validation (16,17) to a first-in-human clinical trial (18). From four ligand-receptors identified in terminal patient, two are ubiquitous and previously reported (integrin α4/annexinA4 and cathepsin B/apolipoprotein E3) and the other two are specific to white adipose tissue (WAT) (prohibitin/annexin A2) (19) and tumor tissues (RAGE/PR3) (4), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings further support the value of BMTP-11 as prospective drug for treating osteosarcoma, in addition to the preclinical and translational data for other more common solid and hematologic tumors (18,20,21). (13), and the metastatic LM7 cell line was developed by successive reimplants of Saos-2 cells through the lungs of nude mice (17).…”
Section: Il-11rα Is Functionally Involved In Lung Colonization By Humanmentioning
confidence: 55%
“…We have previously designed and validated the tumortargeting small-molecule drug BMTP-11 (18), which consists of a functional IL-11Rα-binding peptide (CGRRAGGSC) (15) fused to the apoptosis-inducing peptidomimetic D (KLAKLAK) 2 (19). The antitumor activity of BMTP-11 has been previously evaluated in preclinical models of solid tumors with propensity to metastasize to bone, such as prostate cancer (20) and lung cancer (21), and also in hematologic malignancies primarily originated within the bone marrow cavity, such as leukemia (18); moreover, we have recently reported a first-in-man clinical trial in patients with metastatic prostate cancer (20).…”
Section: Il-11rα Is Functionally Involved In Lung Colonization By Humanmentioning
confidence: 99%
“…Additional examples include Angiopep, a peptide used to target nanoparticles loaded with therapeutic molecules to brains in e.g. Parkinson's disease 14 , the tumor homing NRG-peptide fused together with tumor necrosis factor α (TNFα) to induce anti-tumor reactions towards tumor cells 37,38 , interleukin-11 (IL-11) mimic peptide motif fused together with apoptosis inducing peptide sequence to halt tumor growth 39 and RGR peptide expressed together with LIGHT protein to stabilize leaky, non-functional blood vessels 40 .…”
Section: Conjugated Delivery -Multi-functional Recombinant Proteinsmentioning
confidence: 99%